Advances in high-speed atomic force microscopy (HS-AFM) reveal dynamics of transmembrane channels and transporters. (August 2019) - Heath, George R; Scheuring, Simon
Highlights: HS-AFM detects conformational changes of unlabeled membrane proteins. In situ responses to pH, ligands, temperature and light can be visualized. Developments in techniques now allow microsecond temporal resolution. Abstract : Recent advances in high-speed atomic force microscopy (HS-AFM) have made it possible to study the conformational dynamics of single unlabeled transmembrane channels and transporters. Improving environmental control with the integration of a non-disturbing buffer exchange system, which in turn allows the gradual change of conditions during HS-AFM operation, has provided a breakthrough toward the performance of structural titration experiments. Further advancements in temporal resolution with the use of line scanning and height spectroscopy techniques show how high-speed atomic force microscopy can measure millisecond to microsecond dynamics, pushing this method beyond current spatial and temporal limits offered by less direct techniques.